Invariant Regions and Global Existence of Uniqueness Weak Solutions for Tridiagonal Reaction-Diffusion Systems - BARROUK, Nabila; ABDELMALEK, Karima; REDJOUH, Mounir (Studia Universitatis Babeș-Bolyai Mathematica, 2024)
In this paper we study the existence of uniqueness global weak solutions for m × m reaction-diffusion systems for which two main properties hold: the positivity of the weak solutions and the total mass of the components are preserved with time. Moreover, we suppose that the non-linearities have critical growth with respect to the gradient. The technique we use here in order to prove global existence is in the same spirit of the method developed by Boccardo, Murat, and Puel for a single equation. Mathematics Subject Classification (2010): 35K57, 35K40, 35K55. Received 13 November 2021; Accepted 10 April 2022.